Organizational Conflict Management Styles among Secondary Schools Principals at Mafraq Kasbah from teachers Point of View - Shawaqfah, Ayat Yousef; Elkhateeb, Tasneem Abdullah (Journal of Educational and Psychological Sciences, 2022)
This study aimed at revealing managing organizational conflict styles among the principals of public secondary schools in the Directorate of Education of the Kasbah al-Mafraq region. The descriptive methodology was relied upon by applying the questionnaire tool to the sample of 325 teachers from public secondary schools in the Directorate of Education of the Kasbah Al-Mafraq region in the 2021/2022 school year. The results showed that the styles of organizational conflict management in governmental schools in the Directorate of Education in the Mafraq Kasbah from the teachers’ point of view came to a high degree and in all its fields (3.76), and they were in order as follows (cooperation (3.86), pacification and settlement (3.79), concession (3.75), competition (3.71), avoidance (3.70). The results also showed that there were no statistically significant differences in the methods of organizational conflict due to the effect of gender in all methods except for the avoidance method, and the waiver method. The differences came in favor of males, there were no statistically significant differences due to years of experience variable in all methods except for the avoidance method, and the differences came in favor of less than 5 years. Based on the results of the study, the researcher recommended the necessity of consolidating the concepts of organizational culture and its dimensions, enhancing the school staff’s awareness of its importance and its impact on the high performance of them, deepening school principals’ understanding of organizational conflict, and increasing their awareness of how to diagnose conflict, and how to manage it using different methods.
Keywords: Organizational Culture; Organizational Conflict; Secondary School Principals; Mafraq; Jordan